A sequence of abrupt climatic fluctuations in the north-eastern Caribbean related to the 8.2 ka event - Vieten, Rolf; Warken, Sophie F.; Winter, Amos; Scholz, Denis; Zanchettin, Davide; Black, David; Lachniet, Matthew (The Holocene, 2024)
A speleothem collected from Palco Cave (Puerto Rico) spans the 8.2 ka event, a time interval associated with fluctuations of Atlantic Ocean circulation and possible drying in the Caribbean region. While stalagmite δ18O, δ13C, and Mg/Ca data do not show a sustained change in mean state over the 8.2 ka event, the proxies provide robust evidence for three abrupt fluctuations toward drier conditions in rapid succession, each lasting less than two decades, occurring at 8.20, 8.14, and 8.02 ka BP. A cave monitoring program at Palco Cave supports the interpretation of the speleothem proxy records. Because changes in the position of the Intertropical Convergence Zone (ITCZ) are directly coupled to sea-surface temperature variations in the North Atlantic, we hypothesize that cold events in the North Atlantic temporarily limited the northward migration of the ITCZ and tropical rain belt in boreal summer during these abrupt drying periods. The speleothem record suggests that the 8.2 ka event was associated with rapid rainfall fluctuations in the northern Caribbean followed by a comparably warm and wet phase after the 8.2 ka event. This enhanced variability during the transitional period of the deglaciation appears to be linked to a fast coupling between interacting oceanic and atmospheric processes. This involves, in particular, the Atlantic Meridional Overturning Circulation in modulating interhemispheric heat transport.